Taxonomic and faunistic notes on the genus Trichotichnus from Korea (Coleoptera, Carabidae, Harpalinae, Harpalini) - Dooyoung Kim; Sang Jae Suh (Biodiversity Data Journal, 2022)
Trichotichnus Morawitz, 1863 is a genus of the subtribe Harpalina, comprising more than 260 species worldwide. In Korea, nine species of the nominotypical subgenus are listed in the Korean catalogue (National Institute of Biological Resources 2019), while seven species of the nominotypical subgenus are listed to occur in Korea according to the Palaearctic catalogue (Kataev and Wrase 2017). Therefore, the checklist of the Korean species of the genus Trichotichnus needs to be revised.In the course of taxonomic studies on Trichotichnus species from Korea, two unrecorded species are identified: Trichotichnus (Bottchrus) nanus and Trichotichnus (Trichotichnus) vespertinus. In addition, the distribution of a poorly known species, T. (T.) miser, is firstly recognized in the southern part of Korea. Along with the description of the newly-recorded species, a checklist of the Korean species of the genus Trichotichnus is revised. As for the checklist, the distribution of T. (Iridessus) lucidus and T. (T.) leptopus in Korea is re-discussed, and T. (T.) leptopus is excluded from the Korean fauna. Lastly, additional distribution records for the following species are provided: T. (I.) lucidus, T. (T.) longitarsis, T. (T.) nishioi, and T. (T.) noctuabundus.